Chemotherapy impairs skeletal muscle mitochondrial homeostasis in early breast cancer patients. Issue 3 (4th April 2022) - Mallard, Joris; Hucteau, Elyse; Charles, Anne‐Laure; Bender, Laura; Baeza, Claire; Pélissie, Mathilde; Trensz, Philippe; Pflumio, Carole; Kalish‐Weindling, Michal; Gény, Bernard; Schott, Roland; Favret, Fabrice; et al.
Abstract: Background: Chemotherapy is extensively used to treat breast cancer and is associated with skeletal muscle deconditioning, which is known to reduce patients' quality of life, treatment efficiency, and overall survival. To date, skeletal muscle mitochondrial alterations represent a major aspect explored in breast cancer patients; nevertheless, the cellular mechanisms remain relatively unknown. This study was dedicated to investigating overall skeletal muscle mitochondrial homeostasis in early breast cancer patients undergoing chemotherapy, including mitochondrial quantity, function, and dynamics. Methods: Women undergoing (neo)adjuvant anthracycline‐cyclophosphamide and taxane‐based chemotherapy participated in this study (56 ± 12 years). Two muscle biopsies were collected from the vastus lateralis muscle before the first and after the last chemotherapy administration. Mitochondrial respiratory capacity, reactive oxygen species production, and western blotting analyses were performed. Results: Among the 11 patients, we found a decrease in key markers of mitochondrial quantity, reaching −52.0% for citrate synthase protein levels ( P = 0.02) and −38.2% for VDAC protein levels ( P = 0.04). This mitochondrial content loss is likely explained by reduced mitochondrial biogenesis, as evidenced by a decrease in PGC‐1α1 protein levels (−29.5%; P = 0.04). Mitochondrial dynamics were altered, as documented by a decrease in MFN2 protein expression (−33.4%; P = 0.01), a key marker of mitochondrial outer membrane fusion. Mitochondrial fission is a prerequisite for mitophagy activation, and no variation was found in either key markers of mitochondrial fission (Fis1 and DRP1) or mitophagy (Parkin, PINK1, and Mul1). Two contradictory hypotheses arise from these results: defective mitophagy, which probably increases the number of damaged and fragmented mitochondria, or a relative increase in mitophagy through elevated mitophagic potential (Parkin/VDAC ratio; +176.4%; P < 0.02). Despite no change in mitochondrial respiratory capacity and COX IV protein levels, we found an elevation in H2 O2 production ( P < 0.05 for all substrate additions) without change in antioxidant enzymes. We investigated the apoptosis pathway and found an increase in the protein expression of the apoptosis initiation marker Bax (+72.0%; P = 0.04), without variation in the anti‐apoptotic protein Bcl‐2. Conclusions: This study demonstrated major mitochondrial alterations subsequent to chemotherapy in early breast cancer patients: (i) a striking reduction in mitochondrial biogenesis, (ii) altered mitochondrial dynamics and potential mitophagy defects, (iii) exacerbated H2 O2 production, and (iv) increased initiation of apoptosis. All of these alterations likely explain, at least in part, the high prevalence of skeletal muscle and cardiorespiratory deconditioning classically observed in breast cancer patients.